2022
DOI: 10.3390/ijms231911293
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ATP Production Influences Inorganic Polyphosphate Levels in Non-Athletes’ Platelets at the Resting State

Abstract: Platelets produce inorganic polyphosphate (polyP) upon activation to stimulate blood coagulation. Some researchers have linked polyP metabolism to ATP production, although the metabolic linkage is yet to be elucidated. We found evidence for this possibility in our previous study on professional athletes (versus non-athletes), and proposed that the regulatory mechanism might be different for these two groups. To explore this aspect further, we investigated the effects of modulated ATP production on polyP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, we believe that several other factors modulate the therapeutic potential of PRP through potentiation and suppression and are present in individual PRP preparations [30]. The candidate factor that we have recently paid attention to is polyphosphate (polyP) [31][32][33][34][35][36][37]. PolyP is an ancient, but still mysterious, biopolymer that is produced in the mitochondria in the extension of the ATP production line [33,34,38] and stored in the dense granules of platelets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we believe that several other factors modulate the therapeutic potential of PRP through potentiation and suppression and are present in individual PRP preparations [30]. The candidate factor that we have recently paid attention to is polyphosphate (polyP) [31][32][33][34][35][36][37]. PolyP is an ancient, but still mysterious, biopolymer that is produced in the mitochondria in the extension of the ATP production line [33,34,38] and stored in the dense granules of platelets.…”
Section: Introductionmentioning
confidence: 99%
“…The candidate factor that we have recently paid attention to is polyphosphate (polyP) [31][32][33][34][35][36][37]. PolyP is an ancient, but still mysterious, biopolymer that is produced in the mitochondria in the extension of the ATP production line [33,34,38] and stored in the dense granules of platelets. Upon platelet activation, polyP is released alongside growth factors, and this impacts the immunological functions of platelets in addition to hemostatic function [32].…”
Section: Introductionmentioning
confidence: 99%
“…PolyP influences ATP levels in tumor cells by interacting with cellular processes related to energy metabolism, specifically by modulating the activity of ATP synthase, the enzyme responsible for ATP production in the mitochondria [ 21 , 22 ]. Previous studies have shown that polyP can directly interact with ATP synthase, inhibiting its activity and subsequently reducing ATP production [ 20 , 41 ]. In our previous study, we reported that the cellular ATP content did not increase after X‐ray irradiation in polyP‐treated cells, which led to the upregulation of their radiosensitivity [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [7][8][9], pure water was found to be the most suitable solution for platelet suspensions for fluorometric polyP quantification. Furthermore, in a preliminary study, we found that platelet suspensions, including the fixative, produced insoluble compounds after thawing and interfered with polyP quantification.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
“…To overcome this issue, we optimized the preservation conditions for human platelets based on previously reported quantification methods [7][8][9]. Among several possible protocols, fixation, removal of fixative, replacement with pure water, and preservation at −80 °C appear to be essential elements for successful preservation.…”
Section: Introductionmentioning
confidence: 99%